Microstructure, phase formation and hardness investigation of argon arc melted Al-Co-Cr-Fe-Ni and Al-Cu-Cr-Fe-Ni Highentropy Alloys (HEA) with elemental additions / Rafidah Razuan - Razuan, Rafidah (Institute of Graduate Studies, UiTM, 2017)
Traditional alloying is one of the methods to enhance the performance of pure metals by adding other metals or non-metals. However, as multiple alloying elements in an alloy may lead to the formation of many intermetallic compounds with complex microstructures and poor mechanical properties, new types of metallic alloys called High Entropy Alloy (HEA) with at least 5 elements with equimolar ratios were developed. This thesis reports the microstructural studies, mechanical properties and thermal properties of AlCuCrFeNiTixNby; (x and y= 0.5, 1.0, 1.5), AlCoCrFeNiZrx; (x= 0.2, 0.4, 0.6, 0.8, 1.0) and AlCoCrFeNiMoxNby; (x and y= 0.1, 0.2, 0.3) HEAs that have been prepared using Ar arc melting technique. Effect of adding elements with large atomic radius, nano precipitate formation and high melting point on the phase formation, microstructural development and mechanical properties of HEAs prepared in this study were investigated in detail. Thermodynamic calculations and structural parameters for HEA phase formation criteria were carried out and correlated with the experimental results of the HEAs prepared in this study.